“VAI TU E FAZE O MESMO” – A SUPERAÇÃO DOS CONFLITOS ENTRE JUDEUS E GENTIOS NOS ESCRITOS LUCANOS POR MEIO DA VISÃO DO ESTRANGEIRO COMO MODELO DE FÉ: UM OLHAR A PARTIR DE LUCAS 10.25-37 - MOREIRA, THIAGO SOUZA (2019)
The foreigner is a character who receives special attention throughout the biblical writing. The Old Testament contains several passages in which the concern for the foreigner is revealed, mainly because the people of Israel themselves were foreigners in Egypt (Exodus 22.21; 23.9; Deuteronomy 10.19). The New Testament also presents passages that advocate care for foreigners and their value. Thus, the foreigner in the Lucan writings is the object of this research, starting from the text of Luke 10: 25-37, the well-known parable of the Good Samaritan. However, despite the passages cited above, the biblical literature also demonstrates the conflicts that existed between Jews and foreigners and the difficulty of accepting these foreigners as members of equal rights in early Christianity. For this reason, the objective of this research is to analyze how the Lucan community was challenged to overcome the problem of foreign acceptance. This analysis will consider the influence of foreigners in the shaping of early Christianity, check existing tensions regarding the acceptance of these foreigners and demonstrate how the foreigner acceptance issue is crucial to the understanding of the Good Samaritan parable and of the Lucan writings as a whole. Therefore, this research is intended to demonstrate that the Lucan community had difficulties in accepting the foreigner and, for this reason, the Gospel of Luke and the book of the Acts of the Apostles present, several times, a defense of these foreigners by proposing that to follow Christ implies loving and embracing the foreigner.